Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Modification of shrimp tropomyosin properties for improved functional performance: TGase modification and polyphenol-beta-glucan modification - Shiqi Liu; Ru Meng; Kexin Jiang; Yinuo Bai; Zhenxing Li; Lingyi Liu; Jin Wang; Lianliang Liu (Food Chemistry, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

On-site rapid detection method for Cryptolestes ferrugineus(Coleoptera: Laemophloeidae) based on recombinase polymerase amplification technology - Zhang Ru; Bai Yueliang; Bai Kaixu; Wang Hongjun; Zhao Chao; Yan Lei; Duangsamorn Suthisut; L.V. Jianhua; Zeng Fangfang; Zhang Meng; Bai Chunqi (Journal of Stored Products Research, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

Synergistic effects of phenylsilane and isopropyl titanate-modified montmorillonite nanofillers on the thermal and flame-retardant properties of PVA films - Jing-Yao Xiao; Lei Huang; Shi-Xiang Xiong; Jian-Feng Lan; Ru-Xin Chen; Long-Long Jin; Ze-Chao You; Bai-yi Chen; Xian-Hui Zhang (Applied Clay Science, 2026)

Rhizosphere microbial diversity and inoculation potential for the endangered opisthopappus taihangensis - Yanyan Han; Lihui Zhang; Qiantong Ru; Juan Song; Bianxia Bai; Shan Jin; Jiahong Ren (Plant and Soil, 2026)

Functional homogenization of terrestrial mammals outside protected areas in the Hengduan Mountains, China - Xueyou Li; Wenqiang Hu; Kenneth Otieno Onditi; Quan Li; Zhechang Hu; Ru Bai; Yang Liu; Hongjiao Wang; Xuelong Jiang (Conservation Biology, 2026)
Despite the crucial role of human impacts on biodiversity loss, many assessments of this loss focus on single metrics, such as species richness, and overlook the multidimensional effects of human activities. Because of its importance to ecosystem functioning, we investigated the functional diversity of medium‐ and large‐sized mammal assemblages in protected and unprotected mountain forests in the Hengduan Mountains of southwest China. We hypothesized that anthropogenic pressures outside protected areas (PAs) favor generalist species and lead to functionally homogenized assemblages compared with assemblages inside PAs. Using generalized dissimilarity models, we also examined the key drivers shaping patterns of functional β diversity in these landscapes. Outside PAs, functional richness was markedly lower, trait space was significantly more homogeneous, and nestedness β diversity was more prevalent (57.6%) than inside PAs, clear indications of functional homogenization. Anthropogenic variables consistently outweighed environmental gradients and spatial distance in explaining variation in functional β diversity. Our results demonstrate that anthropogenic pressure affects trait composition in ways that species counts alone do not fully capture, emphasizing the importance of conservation strategies that protect both functional integrity and taxonomic diversity.

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

Construction of WO3/ZnIn2S4 Z-scheme heterojunction by electrostatic self-assembly to enhance charge separation and reactive oxygen species generation - Mengge Yan; Tingting Liu; Yushan Hu; Wenlong Bai; Mingfei Wei; Yuxuan Zhang; Xusheng He; Ru Li (Journal of Water Process Engineering, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Permian Ridge Subduction-Related Magmatism in the Chinese Altai: Insights from Geochronology and Geochemistry of the Jiangjunshan Pluton - Shi-Heng Bai; Ru-Xiong Lei; Matthew J. Brzozowski; Zhen-Hua Wang; Wei Wang; Chang-Zhi Wu (Journal of Earth Science, 2025)

Significant but overlooked manganese oxides mediate anaerobic ammonium oxidation processes in the littoral zone - Jiahui Deng; Shanghua Wu; Zhihui Bai; Shijie Wang; Chang Ru; Tsing Bohu; Xuliang Zhuang (Limnology and Oceanography, 2025)
The littoral zone of lakes is recognized as hotspots of biogeochemical cycles. While the coupling of Fe(III) reduction and ammonium oxidation is acknowledged as an important nitrogen loss pathway, the role of anaerobic ammonium oxidation mediated by Mn oxides (Mnammox) remains uncertain. In this study, we conducted a 15 NH 4 + isotopic incubation experiment and applied Mn oxides amended treatment to investigate the role of Mnammox in the lake littoral zone with respect to the N biogeochemical cycle. Our findings confirmed the widespread presence of Mnammox in the littoral zone of Baiyangdian Lake, the largest freshwater lake in the North China Plain. The sediment exhibited an average 30 N 2 production rate of 19.91 μ g kg −1 d −1 , accounting for approximately 2.0% of total nitrogen loss in situ. Significant nitrate production was also observed with a rate of 0.26 mg N kg −1 d −1 , highlighting the role of Mnammox as a potential source of nitrate under anaerobic conditions. Furthermore, we identified a key threshold of 3.15 g kg −1 dry weight sediment MnO 2 amendment, roughly 20 times the in situ MnO 2 content, which most significantly enhanced the Mnammox process. Sediment Mn oxides content, moisture content, and pH were the main stimulators for the Mnammox process, with unique microbial groups. This work underscores the importance of Mnammox in the lake littoral zone, illuminating the Mn–N coupling that drives multi‐element cycles in this critical environment.

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Underwater-adhesive and mechanically reinforced porous amidoxime hydrogel for fast and selective uranium extraction from seawater - Xue Bai; Pan Wang; Ru Feng; Jianming Pan; Yonghui Sun (Desalination, 2025)

Effects of curcumin on jejunal morphology and intestinal integrity of broiler under heat stress - Ding-Ding Zhang; Meng-Ru Xue; Yu-Ting Liu; Hong-Jie Cui; Ding-Ping Bai (Journal of Thermal Biology, 2025)

Corrigendum to “Fingerprint spectrum retrieval of ultra-low amino acids concentration achieved by angle tunable carbon nanotube terahertz metasurfaces” [Chem. Eng. J. 520 (2025) 166389] - Xiang Zhang; Yue Wang; Jiaxue Li; Yizhuo Fan; Gengyu Bai; Xiangdong Chen; Yumeng Ru; Chang Wang (Chemical Engineering Journal, 2025)

Fingerprint spectrum retrieval of ultra-low amino acids concentration achieved by angle tunable carbon nanotube terahertz metasurfaces - Xiang Zhang; Yue Wang; Jiaxue Li; Yizhuo Fan; Gengyu Bai; Xiangdong Chen; Yumeng Ru; Chang Wang (Chemical Engineering Journal, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Ilimaquinone induces apoptosis in gastric cancer cells by inhibiting the signal transducer and activator of the transcription 3 pathway - Jui-Hsin Su; Li-Yuan Bai; Chia-Yung Wu; Chia-Hsien Feng; Jing-Ru Weng (Chemico-Biological Interactions, 2025)

Systematic review of natural coumarins in plants (2019–2024): Chemical structures and pharmacological activities - Ze-Dong Nan; Ying Shang; Yi-Dong Zhu; Hui Zhang; Ru-Ru Sun; Jing-Jing Tian; Zhi-Bo Jiang; Xiao-Li Ma; Changcai Bai (Phytochemistry, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Molecular insights into water balance disruption as a pest control strategy for Rhyzopertha dominica (F.) - Yueliang Bai; Guiyao Wang; Ru Zhang; Chunqi Bai; Jianhua Lv; Meng Zhang (Journal of Stored Products Research, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Granitoid genesis and related rare metal mineralization of the Shihuiyao Rb–Ta–Nb deposit in the Southern Great Xing’an Range, NE China - Shi-Heng Bai; Yu Huang; Zhi-Jie Feng; Matthew J. Brzozowski; Yao-Hui Jiang; Ru-Xiong Lei; Chang-Zhi Wu (Gondwana Research, 2025)

Investigation on the synergistic effects and thermokinetic analyses during co-combustion of corn stalk and polyethylene plastic: Effect of heating rate and placement method - Mengjie Liu; Bin Han; Jin Bai; Jiayao Ru; Xuetao Wang; Lili Xing; Haojie Li; Siyu Lv; Aopeng Gao; Yiming Wang; Lingxue Kong; Zongqing Bai; et al. (Fuel, 2025)

Differentiation revelation of wine quality induced by maceration technology under the mediation of environmental factors and microbial community - Manman Gao; Shuo Yu; Jianing Bai; Ru Chen; Yunjie Li; Liping Du; Lijuan Ma; Huiling Zhang; Xiaoju Tian (Food Bioscience, 2025)

Cell-permeable PI3 kinase competitive peptide inhibits KIT mutant mediated tumorigenesis of gastrointestinal stromal tumor (GIST) - Zongying Jiang; Yue Guo; Jun Shi; Shaoting Zhang; Liangying Zhang; Yapeng Wang; Guofu Li; Ru Bai; Hui Zhao; Jianmin Sun (Molecular Biology Reports, 2024)

Adsorption Kinetics and Stabilization Effects of Various Forms of Phosphorus on Schwertmannite - Shuqin Bai; Ru Ya; Shuxuan Chen; Niqi Ao; Yiwen Wu; Qiyao Sun; Han Yang; Shuangfeng Zhao (Water, Air, & Soil Pollution, 2024)

Unraveling the effect of combined heat and high-pressure homogenization treatment on the improvement of chickpea protein solubility from the perspectives of colloidal state change and structural characteristic modification - Yu Wang; Jing-jing Yuan; Ya-ru Zhang; Xing Chen; Jia-le Wang; Bo Chen; Ke Li; Yan-hong Bai (Food Chemistry, 2024)

Cadmium Treatment Affected the Growth and Physiology of Larix Olgensis Seedlings, the Chemical Properties of Haplic Cambisols and Toxicity Threshold Determination - Haixia Wang; Kunshu Yao; Jiaxin Ru; Jiagui Guo; Ding Liu; Yunlong Liu; LingYun Bai; Jixiang Lin; Chengbo Gu; Jinfeng Song (Journal of Soil Science and Plant Nutrition, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Effects of land use and land cover change under shared socioeconomic pathways on future climate in the Yellow River basin, China - Xutong Ru; Longxin Qiao; Haopeng Zhang; Tianqi Bai; Ruiqi Min; Yaobin Wang; Qianfeng Wang; Hongquan Song (Urban Climate, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Scaling and cleaning of silica scales on reverse osmosis membrane: Effective removal and degradation mechanisms utilizing gallic acid - Shuqin Bai; Jue Han; Niqi Ao; Ru Ya; Wei Ding (Chemosphere, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

The application of static digestive models simulating the digestion system of infants and young children for the development of accessory food: Current status and future perspective - Jing Lin; Caiyu Liu; Ru Bai; Jinzhu Pang; Junan Li; Chi Zhang; Xinqi Liu; He Li; Sumei Hu (Trends in Food Science & Technology, 2024)

A novel hydrangea-like magnetic composite Fe3O4@MnO2@ZIF-67 for efficient selective adsorption of Pd(II) from metallurgical wastewater - Xue Jiang; Yu Zhou; Haiou Chen; Ru Zhang; Junhui Yu; Shixiong Wang; Fengzhi Jiang; Huiping Bai; Xiangjun Yang (Chemosphere, 2023)

From air to airway: Dynamics and risk of inhalable bacteria in municipal solid waste treatment systems - Ru Fang; Tian Chen; Zhibang Han; Wenhui Ji; Yudan Bai; Zhipeng Zheng; Yinglong Su; Ling Jin; Bing Xie; Dong Wu (Journal of Hazardous Materials, 2023)

Exploration of using acoustic vibration technology to non-destructively detect moldy kernels of in-shell hickory nuts (Carya cathayensis Sarg.) - Qing-li Han; Bai-xue Long; Xue-jun Yan; Wu Wang; Feng-ru Liu; Xue Chen; Fei Ma (Computers and Electronics in Agriculture, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A hybrid optimized model for predicting evapotranspiration in early and late rice based on a categorical regression tree combination of key influencing factors - Long Zhao; Shunhao Qing; Jiayi Bai; Haohao Hao; Hui Li; Yi Shi; Xuguang Xing; Ru Yang (Computers and Electronics in Agriculture, 2023)

Effects of exposure to chlorinated paraffins on human health: A scoping review - Jing-Wen Huang; Ya-Ying Bai; Mohammed Zeeshan; Ru-Qing Liu; Guang-Hui Dong (Science of The Total Environment, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Effect of agricultural soil wind erosion on urban PM2.5 concentrations simulated by WRF-Chem and WEPS: A case study in Kaifeng, China - Haopeng Zhang; Hongquan Song; Xiaowei Wang; Yaobin Wang; Ruiqi Min; Minghui Qi; Xutong Ru; Tianqi Bai; Hua Xue (Chemosphere, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Pasture degradation impact on soil carbon and nitrogen fractions of alpine meadow in a Tibetan permafrost region - Zi-Qiang Yuan; Qing-Bai Wu; Xin Song; Xiao-Jin Jiang; Si-Ru Gao; Qing-Feng Wang; Guo-Yu Li (Journal of Soils and Sediments, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

The transcription factor MYB15 is essential for basal immunity (PTI) in Chinese wild grape - Yangyang Luo; Ru Bai; Jing Li; Weidong Yang; Ruixiang Li; Qingyang Wang; Guifang Zhao; Dong Duan (Planta, 2019)

The complete chloroplast genome of Calycanthus chinensis, an endangered species endemic to China - Xiaodan Chen; Jia Yang; Hao Zhang; Ru Bai; Xiao Zhang; Guoqing Bai; Panfeng Dai; Guifang Zhao (Conservation Genetics Resources, 2019)

Characterization of the complete chloroplast genome sequence of an endangered elm species, ulmus gaussenii (Ulmaceae) - Qing Zhang; Hao Zhang; Qiang Li; Ru Bai; Er Ning; Xia Cai (Conservation Genetics Resources, 2019)

A specific allele of MYB14 in grapevine correlates with high stilbene inducibility triggered by Al3+ and UV-C radiation - Ru Bai; Yangyang Luo; Lixin Wang; Jing Li; Kerun Wu; Guifang Zhao; Dong Duan (Plant Cell Reports, 2019)

The complete chloroplast genome sequence of the white strawberry Fragaria pentaphylla - Li-jun Bai; Yun-tian Ye; Qing Chen; Hao-ru Tang (Conservation Genetics Resources, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Molecular cloning and characterisation of two enzymes involved in the rosmarinic acid biosynthesis pathway of Prunella vulgaris L. - Mei Ru; Kunru Wang; Zhenqing Bai; Liang Peng; Shaoxuan He; Tianlin Pei; Yanyan Jia; Hongyan Li; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Induction of DNA base damage and strand breaks in peripheral erythrocytes and the underlying mechanism in goldfish (Carassius auratus) exposed to monocrotophos - Fei Zhao; Bai Wang; Xiaona Zhang; Hua Tian; Wei Wang; Shaoguo Ru (Fish Physiology and Biochemistry, 2015)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

Trends of grain yield and plant traits in Chinese maize cultivars from the 1950s to the 2000s - Xiaoke Ci; Mingshun Li; Jiashun Xu; Zhenyu Lu; Pengfei Bai; Gaolin Ru; Xiaoling Liang; Degui Zhang; Xinhai Li; Li Bai; Chuanxiao Xie; Zhuanfang Hao; et al. (Euphytica, 2012)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Phthalic Acid Induces Oxidative Stress and Alters the Activity of Some Antioxidant Enzymes in Roots of Malus prunifolia - Ru Bai; Fengwang Ma; Dong Liang; Xin Zhao (Journal of Chemical Ecology, 2009)

Identifying the Scale Thresholds for Field-Data Extrapolation via Spatial Analysis of Landscape Gradients - Chi-Ru Chang; Pei-Fen Lee; Mei-Ling Bai; Tzer-Ton Lin (Ecosystems, 2006)